Analysis of the thermal performance of brises as solar control devices in bioclimatic zone 7: a computational simulation-based approach - Celestino, Jean Carlos Harala; Sanches, João Carlos Machado (Scientific Journal ANAP, 2025)
Objective – To critically analyze the effectiveness of the brise-soleil as a solar control element in buildings located in Bioclimatic Zone 7, from the perspective of thermal energy performance.Methodology – Parametrized computational simulations were conducted using the software SketchUp, OpenStudio, and EnergyPlus. Three distinct architectural models were investigated, subjected to different configurations of brise-soleils and solar orientations, in scenarios with and without natural ventilation.Originality/relevance – The research fills a gap in the literature by integrating passive strategies with thermal energy modeling in tropical urban contexts, contributing to the development of more precise guidelines for sustainable buildings.Results – The presence of brise-soleils, especially when combined with cross ventilation and materials with high thermal inertia, significantly reduced the internal thermal load, enhancing thermal comfort and energy efficiency.Theoretical/methodological contributions – The study validates the applicability of computational simulation as a design support tool and offers methodological subsidies for multiscale analyses of thermal performance.Social and environmental contributions – By promoting low-energy-impact architectural solutions, the study fosters sustainable practices and contributes to the mitigation of climate change in urban environments in hot and dry regions.
Keywords: thermal performance; energy simulation; passive strategies; bioclimatic architecture